A Highly Selective Copper–Indium Bimetallic Electrocatalyst for the Electrochemical Reduction of Aqueous CO2 to CO1. (23rd December 2014) - Rasul, Shahid; Anjum, Dalaver H.; Jedidi, Abdesslem; Minenkov, Yury; Cavallo, Luigi; Takanabe, Kazuhiro
Abstract The challenge in the electrochemical reduction of aqueous carbon dioxide is in designing a highly selective, energy‐efficient, and non‐precious‐metal electrocatalyst that minimizes the competitive reduction of proton to form hydrogen during aqueous CO2 conversion. A non‐noble metal electrocatalyst based on a copper‐indium (Cu‐In) alloy that selectively converts CO2 to CO with a low overpotential is reported. The electrochemical deposition of In on rough Cu surfaces led to Cu‐In alloy surfaces. DFT calculations showed that the In preferentially located on the edge sites rather than on the corner or flat sites and that the d‐electron nature of Cu remained almost intact, but adsorption properties of neighboring Cu was perturbed by the presence of In. This preparation of non‐noble metal alloy electrodes for the reduction of CO2 provides guidelines for further improving electrocatalysis.